Oscillation of neutral differential equations with distributed deviating arguments - Candan, T.; Karpuz, B.; Öcalan, Ö. (Нелінійні коливання, 2012)
In this article, we study oscillatory nature of all solutions of a class of neutral differential equations with distributed deviating arguments. Some examples are also included to show the applicability of the results.